The Effect of Shifting Large and Medium-Sized Industry Agglomeration on the Economic Development in Kanti Region in 2003-2018 - Ahmad Firman Maulana; Ekaria Ekaria (Politeknik Statistika STIS, 2021)
The development of real Gross Domestic Regional Product (GDRP) 2010 of all cities in Kanti region increased during 2003-2018. However, when viewed the growth rate in aggregate, it slowed during the period 2010-2018. One of the causes is the shift of large and medium-size industry (LMI) agglomeration from Kanti region to Kangga region. This study aims to find out the location and the dynamics of the shift of LMI agglomeration using the Hoover-Balassa index that is presented through thematic maps. In addition, the study also analyses the effect of the shift of LMI agglomeration and other factors on economic growth in Kanti region using the regression analysis of panel data. The individual units used are five administrative cities in the Kanti region with annual units from 2003 to 2018. Fixed effect model with seemingly unrelated regression (FEM-SUR) is used to estimate the parameters of the economic growth model in Kanti region. The results showed that Kanti region was agglomerated in North Jakarta and East Jakarta. Labor-intensive potential factor has a negative and significant effect, while the labor productivity of LMI and domestic investment has a positive and significant effect on economic growth in Kanti region. North Jakarta is an area that despite the shift of LMI agglomeration but still able to increase its economic growth, while East Jakarta has decreased. So, the Provincial Government of Jakarta need to adapt the implementation of LMI agglomeration in North Jakarta to encourage economic growth in East Jakarta and West Jakarta in accordance with regional spatial planning for industry.